Alkoholkonsum bei Jugendlichen in Deutschland - Ergebnisse aus EsKiMo - Kohler, Simone; Richter, A.; Lampert, T.; Mensink, G. B. M. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2009)
The study EsKiMo (Eating study as a KiGGS Module) was conducted from January to December 2006 as a follow-up study of the German Health Interview and Examination Survey for Children and Adolescents (KiGGS). With data from this study, the alcohol consumption of adolescents in Germany is explored. Interviews were conducted with 1272 adolescents, aged 12 to 17 years, using the dietary assessment software DISHES which is based on the diet history method. From consumption data of the previous four weeks, means and percentiles of the average daily consumption of alcoholic beverages as well as pure alcohol intake were calculated, stratified by age, sex, new and old federal states, social status, type of school, and migration background. Furthermore, the associations of these variables with alcohol intake were determined in univariate and multiple linear regression analyses. The highest amount of alcoholic beverages is consumed as beer. Among 16- to 17-year-olds, boys consume on average 10.4 g alcohol and girls 3.8 g alcohol per day and even 11% of boys and 6% of girls exceed the tolerable upper intake levels for adults. Alcohol consumption increases significantly with age (p< 0.001), boys drink significantly more alcohol than girls of the same age (p< 0.001), and migrants significantly less than non-migrants (p< 0.05). Differences between new and old federal states, social status, and type of school are not statistically significant. Alcohol consumption is high among adolescents, most particular among boys aged 16 to 17 years. Since about a quarter of 12- to 13-year-olds consumed alcohol at least once in the last four weeks, there is a need for action already in this age group. © 2009 Springer Medizin Verlag.
Created from Fastlane, Scopus look-up
Keywords: Adolescents; Alcohol; EsKiMo; Germany; Survey